Mối tương quan giữa phong cách làm cha mẹ và lo âu ở học sinh trung học phổ thông - Lê, Thị Thanh Thuỷ; Phạm, Phương Thanh; Nguyễn, Hữu Đông (Tạp chí Giáo dục, 2025)
Parenting styles have been shown in many studies to influence children development, especially anxiety in children. This article focuses on analyzing anxiety in high school students, parenting styles and the relationship between parenting style and anxiety in high school students. The data of this article is drawn from a research survey of 302 parents and 470 students at 3 high schools in Cam Pha city, Quang Ninh province. The main survey tool is a questionnaire, including the PAQ scale on parents' parenting style and the AAS scale (student academic anxiety scale). This survey was conducted in December 2024. The results showed that 90% of students showed anxiety at different levels, 72% of parents had a democratic style, the rest had an authoritarian style and a liberal style. There is a correlation between authoritarian parenting style and anxiety in high school students. This study provides a basis for psychologists, educators and parents to support and intervene to reduce anxiety in students based on understanding anxiety and adjusting communication style.